Studying Periostin as a Diagnostic Marker in Sera of Iraqi Patients Hypothyroidism - Khalil Ibrahim, Duha; Othman Farhan, Layla (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Hypothyroidism is one of the most common thyroid diseases in adults. Hypothyroidism is a condition that results from a deficiency of thyroid hormone and can range from being asymptomatic to life-threatening. A decrease in thyroid hormone production in the thyroid gland, a shortage of pituitary thyroid stimulating hormone, or a hypothalamic Thyrotropin-releasing hormone deficiency can cause hypothyroidism. Thyrotropin-releasing hormone deficiency Periostin is classified as both an extracellular matrix protein and a matricellular protein that belongs to the fasciclin family. As a matricellular protein, Postn plays a crucial role in the growth and maintenance of tissues and organs. Due to the limited research on the effects of Postn on the thyroid gland, the aim of this study is to investigate the relationship between Postn and hypothyroidism. The 120 samples were divided into two groups: 80 patients with hypothyroidism and 40 healthy people. Postn levels significantly increased in the hypothyroidism group compared to the control group (p ˂ 0.001). The results indicate that Postn can be a sensitive and accurate marker for diagnosing hypothyroidism in Iraqi patients.